(untitled) (Rhythmos, 2016)
Background: In recent years, there has been considerable research in the field of post-resuscitation care. Recent guidelines recommend early coronary angiography and percutaneous coronary intervention (PCI) as the best strategy in survivors of out-of-hospital cardiac arrest (OOHCA) with ST elevation myocardial infarction (STEMI). However, there are no decisive data for patients who do not exhibit clinical and ECG criteria suggestive of STEMI. We sought to review current evidence regarding the predictive factors of positive coronary angiography and the role of early PCI in an OOHCA setting. Methods & Results: Between 1995 & 2014, we identified 35 studies reporting on adult survivors of OOHCA who underwent coronary angiography and PCI. In total, there are over 16,000 patients included in reported series of resuscitated OOHCA victims who have undergone coronary angiography and PCI when indicated. PCI was successful in 92% (51-100%) of the attempted cases. The survival rate was 64% (22% - 88%) with a satisfactory neurological outcome at follow-up that varied from 47-96%. As the survival benefit seems to be time dependent, the selection of which patients are candidates for early PCI is under considerable research. Predictive factors for positive coronary angiography and outcome were ventricular fibrillation, history of coronary heart disease and diabetes, ST elevation on ECG, male gender, and intact brain stem functions. Negative predictive factors were normal ECG on admission or plain repolarization abnormalities, and loss of brain stem functions. Conclusions: Early coronary angiography and PCI is a promising management strategy in the OOHCA setting. As there is evidence that the survival benefit from PCI is time dependent, the research is still ongoing in identifying which patients would benefit most from an aggressive revascularization approach.